Flexible Bioelectronics: Flexible Bioelectronic Devices Based on Micropatterned Monolithic Carbon Fiber Mats (Adv. Mater. Technol. 2/2020). Issue 2 (10th February 2020) - Vomero, Maria; Gueli, Calogero; Zucchini, Elena; Fadiga, Luciano; Erhardt, Johannes B.; Sharma, Swati; Stieglitz, Thomas
Abstract : Flexible, cloth‐like, polymer‐derived carbon fiber mats, that are embedded in polyimide, are presented in article number 1900713 by Swati Sharma, Thomas Stieglitz and co‐workers. This scalable, monolithic manufacturing method eliminates any joints or metal interconnects and creates compliable, implantable electrocorticography (ECoG) electrode arrays that show good biocompatibility and performance in rat models.